IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH LOKAL DALAM MENGEMBANGKAN KOMPETENSI EKOLOGIS PADA PEMBELAJARAN IPS - Muhaimin Muhaimin (Sosio-Didaktika: Social Science Education Journal, 2015)
Human and the environment is an integrated system to form ecosystems in which humans are physically and socially dependent. One concern is the content of social studies related to the ecological interactions between humans and the environment. In the factual context, ecological competence developed in social studies only at the level of knowlegde ecological, moral, and behavior, which has not been valued and embodied in the form of concrete to protect and sustain the environment. The results showed no differences in ecological competence for aspects of knowledge, attitudes, and skills between the pre-test and post-test. The study recommends that the implementation of learning social science education in a broader scope based on local environmental issues are found in everyday life. Schools cultivate ecological competence through the formation of habits, role modeling, and school behavior and culture form a joint motion which is in line with the curriculum green and green living. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1409